Numerical modelling of thermal convection in the Luttelgeest carbonate platform, the Netherlands. (November 2016) - Lipsey, Lindsay; Pluymaekers, Maarten; Goldberg, Tatiana; van Oversteeg, Katrien; Ghazaryan, Lilya; Cloetingh, Sierd; van Wees, Jan-Diederik
Highlights: Luttelgeest carbonate platform shows high temperature anomalies. 3D numerical modelling reproduces thermal anomalies linked to convective fluid flow. Temperature enhancements are critically dependent on platform geometry and permeability. Models have a strong effect on exploration opportunity and risk of prospective areas. Abstract: The presence of convective fluid flow in permeable layers can create zones of anomalously high temperature which can be exploited for geothermal energy. Temperature measurements from the Luttelgeest-01 (LTG-01) well in the northern onshore region of the Netherlands indicate variations in the thermal regime that could be indicative of convection. This thermal anomaly coincides with a 800 m interval of Dinantian carbonates showing signs of increased fracture permeability of 6 10 −14  m 2 . In this study, we reproduce the thermal gradient at LTG-01 using 3D numerical models in order to better understand the interplay between natural fracture permeability and temperature patterns. Numerical models of thermal convection are used to illustrate the role of permeability on the timing of convection onset, convection structure development and resulting temperature patterns. Rayleigh number calculations indicate that convective flow is realistic within the Luttelgeest carbonate platform. The degree and pattern of convection depends strongly on the platform geometry and thickness, permeability structure and geothermal gradient of the convective zone. The spacing of convective upwellings and their thermal anomalies can be well predicted by numerical models that provide evidence for significant convection-driven thermal anomalies. Numerical models can facilitate in exploration workflows to assess thermal variation and location of upwelling zones.